Efficacy of metformin in prevention of paclitaxel-induced peripheral neuropathy in breast cancer patients: a randomized controlled trial - Bakry, Hala M.; Mansour, Noha O.; ElKhodary, Tawfik R.; Soliman, Moetaza M. (Frontiers in Pharmacology, 2023)
Background Paclitaxel-induced peripheral neuropathy (PN) is a serious clinical problem with no approved drug for prevention. This study aimed to examine the neuroprotective effect of metformin against paclitaxel induced PN in breast cancer patients. Methods Patients with confirmed breast cancer diagnosis, who were planned to receive paclitaxel, were randomized to receive either metformin or placebo. Both groups received the standard chemotherapy protocol for breast cancer. Patients started metformin/placebo one week before paclitaxel initiation, and continued study interventions thereafter for nine consecutive weeks. The primary outcome was the incidence of development of grade two or more paclitaxel induced sensory PN. The PN was graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE). Patients’ quality of life (QoL) was assessed by the Functional Assessment of Cancer Therapy/ Gynecologic Oncology Group-Neurotoxicity (FACTGOG-Ntx) subscale. Pain severity was measured by the Brief Pain Inventory Short Form (BPI-SF). Serum levels of nerve growth factor (NGF) and neurotensin (NT) were measured at baseline and at the end paclitaxel treatment. Results Seventy-three patients (36 in the metformin arm and 37 in the control arm) were evaluated. The cumulative incidence of development of grade two or more PN was significantly lower in metformin arm (14 (38.9%) than the control arm (28 (75.7%); P = 0.001). At the end of paclitaxel treatment, patients’ QoL was significantly better in the metformin arm [median (IQR) FACTGOG-Ntx subscale of (24.0 (20.5-26.5)] compared to the control arm (21.0 (18.0-24.0); p = 0.003). The Metformin arm showed lower “average” and “worst” pain scores than those detected in the control arm. At the end of paclitaxel treatment, there was a significant difference in the median serum NGF levels between the two arms, favoring metformin (P < 0.05) while NT serum levels deemed comparable between the two study arms (P = 0.092). Conclusion The use of metformin in breast cancer patients offered a marked protection against paclitaxel induced PN which was translated to better patients’ QoL. https://clinicaltrials.gov/ct2/show/NCT05351021